Soap production: A green prospective. (August 2017) - Félix, Sandra; Araújo, Joana; Pires, Ana Maria; Sousa, Ana Cláudia
Highlights: Reducing the amount of different types of municipal waste. Recycling waste to obtain a useful green soap, which is good quality and cheap. Inspiring community projects meant to convey recycling and ecological approach. Contributing to families' economy and stimulating the use of healthier products. Abstract: A green prospective based on the reuse of waste materials such as almond shells, orange peel and used cooking oil to manufacture soap is presented. In Portugal, thousands of tons of waste are generated from used cooking oil and production of nut shells' residues is growing every year. In addition, the high consumption of citrus fruits, oranges in particular, generates large amounts of citrus peel. Therefore, it is necessary to diversify reuse mechanisms of these wastes, in order to make them back into raw materials. Complying with this trend, this work was carried out by processing and grinding almond shells, treating used oil, processing orange peels and extracting limonene, formulating and producing soap, and performing an acceptance study of the final product. Results validated a high potential of the idea in the field of environmental education, so it can be replicated in practical classes. It can also be useful for waste management, and it can support the development of community projects on an ecological approach.